Penguatan Infrastruktur Jaringan Telekomunikasi sebagai Strategi Akselerasi Pemasaran Digital UMKM: Program Pengabdian Masyarakat pada Siomay Oishii - S.N.M.P. Simamora (Medan Resource Center, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, yet frequently encounter obstacles in adopting digital technology due to infrastructural limitations. Siomay Oishii, a culinary MSME located in Bandung and the partner of this community service program, faced constraints in expanding its market reach and operational efficiency due to limited digital marketing literacy and unstable internet connectivity. This community service program aimed to strengthen telecommunication network infrastructure to support the digital sales and marketing system of Siomay Oishii. The program was implemented in three stages: (1) needs analysis and installation of supporting telecommunication network devices, (2) digital marketing management training, and (3) intensive assistance in online-based sales operations. To contextualize the importance of network infrastructure at the national level, this program was also supported by a public opinion survey on telecommunication network quality perception in Indonesia. The results indicate an improvement in the quality of network connectivity used by the partner, along with an increased capability to independently operate online sales platforms. These outcomes reflect the essential role of telecommunication network infrastructure as a foundation for accelerating digital transformation among culinary MSMEs